Test-takers’ perspectives on consumer genetic testing for hereditary cancer risk - Kilbride, Madison K.; Kessler, Lisa Jay; Cronier, Brigitte; Park, Jacqueline J.; Cacioppo, Cara N.; Beem, Jordyn; Bradbury, Angela R. (Frontiers in Genetics, 2024)
Purpose: With few exceptions, research on consumer genetic testing for hereditary cancer risk has focused on tests with limited predictive value and clinical utility. Our study advances the existing literature by exploring the experiences and behaviors of individuals who have taken modern consumer genetic tests for cancer susceptibility that, unlike earlier tests, screen for medically significant variants.We interviewed 30 individuals who had undergone consumer genetic testing for hereditary cancer risk between 2014 and 2019. We explored participants' pre-test sentiments (7 items), experiences receiving results (5 items), behavioral and health-related changes (6 items), and attitudes and beliefs (3 items). Data were analyzed for thematic content.Results: Most participants reported a personal (n=6) and/or family history (n=24) of cancer, which influenced their choice to pursue testing. Before testing, most participants did not consult with a physician (n=25) or receive genetic counseling (n=23). Nevertheless, the majority felt that they understood test-related information (n=20) and their results (n=20), though a considerable number reported experiencing negative emotions related to their results. Most also shared their results with family members (n=27). Overall, participants' attitudes towards consumer genetic testing for cancer risk were predominantly positive (n=23).This study offers new insights into how individuals use and perceive modern consumer genetic tests for hereditary cancer risk, focusing on their perceptions of the risks, benefits, and limitations of these services. Understanding test-takers' perspectives can potentially inform improvements aimed at ensuring that tests meet users' needs and deliver clinically valuable genetic risk assessments.